In Vivo Confocal Microscopic Observations of Vortex Keratopathy in Patients with Amiodarone-Induced Keratopathy and Fabry Disease - Yasuhito Ikegawa; Atsushi Shiraishi; Yasuhito Hayashi; Akiyoshi Ogimoto; Yuichi Ohashi (Journal of Ophthalmology)
Purpose. To compare the morphology of two types of vortex keratopathy: amiodarone-induced keratopathy and the Fabry disease-associated keratopathy. Patients and Methods. Eight patients who were receiving oral amiodarone therapy and 3 patients with Fabry disease, a mother and her 2 daughters, were examined by slit-lamp biomicroscopy and in vivo confocal microscopy (IVCM) regularly. Results. Amiodarone-induced keratopathy developed in 7 of the 8 patients, and it was detected as early as 7 days by IVCM and 14 days by slit-lamp biomicroscopy. The in vivo confocal microscopic images showed a clustering of corneal epithelial cells with a highly reflective cytoplasm in both types of keratopathy. In the amiodarone-induced keratopathy, the highly reflective epithelial cells were first found at the center of the cornea and then spread to the periphery with increasing time on amiodarone. In Fabry disease, the highly reflective epithelial cells were consistently observed extending from the limbus to the central cornea. Conclusion. These findings suggest that the corneal epithelial cells most likely endocytose amiodarone from the tear film in the amiodarone-induced keratopathy. In Fabry disease, globotriaosylceramide deposits are taken up by the lysosomes of the limbal epithelial stem cells, and they differentiate and migrate to the center of the cornea to form the whorl pattern.